Differences in Neuroticism Between Patients with Glaucoma Who Have Discontinued Visits to Ophthalmologists and Those Who Make Regular Visits: Implications for Adherence to Topical Glaucoma Medications. Issue 2 (December 2016) - Nakano, Tadashi; Kodaka, Fumitoshi; Tsuneoka, Hiroshi
Abstract Introduction Neuroticism is a personality trait often described in individuals with glaucoma (GLC), but is not necessarily representative of the total population of patients. There is a population of patients with GLC who are invisible to clinical ophthalmologists; in other words, those who once have been diagnosed with GLC, but spontaneously stop visiting an ophthalmologist. Little is known about their neuroticism personality trait. In the present study, the authors compared the level of neuroticism between patients no longer visiting an ophthalmologist and those who continue visit them regularly. Methods Patients were assigned to two groups according to the duration of their last visit to an ophthalmologist: theDiscontinued group included those patients who had not visited an ophthalmologist for the last 6 months, and theRegular Visitor group included those patients who continued to make regular visits to an ophthalmologist. The Japanese version of Ten Items Personality Inventory (TIPI-J), a questionnaire specifically used to assess the Big Five personality traits (extraversion, agreeableness, conscientiousness, neuroticism, and openness), was completed by patients through a dedicated website. Results Three-hundred and seventy-three patients with GLC were recruited. The neuroticism score from the TIPI-J in theDiscontinued group was significantly lower than that in theRegular Visitor group (7.63 ± 2.23 vs. 8.23 ± 2.21, respectively;P  = 0.01). No significant difference was found in the other TIPI-J sub-item scores between theDiscontinued and theRegular Visitor groups. Conclusion In this study, the authors showed that neuroticism trait in patients with GLC who have discontinued visiting their ophthalmologists was lower than that in patients who regularly visited them, on the basis of the Big Five personality traits as measured by the TIPT-J. Funding Santen Pharmaceutical Co., Ltd.